A Study of Evolving Neo-Gothic Motifs and Cultural Anxiety in Matt Haig’s The Midnight Library - Kausalya Devi Himani, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
This article examines Matt Haig’s The Midnight Library (2020) as a Neo-Gothic text that reinterprets classical Gothic motifs to explore contemporary cultural anxieties surrounding identity, mental health, and selfhood. In contrast to traditional Gothic fiction, which externalises horror through supernatural elements, Haig’s novel internalises fear, presenting psychological fragmentation, existential uncertainty, and the burden of choice as central sites of Gothic tension. The Midnight Library functions as a liminal space suspended between life and death, where alternative lives emerge as haunting representations of rejected and unsuccessful identities. Engaging Julia Kristeva’s theory of abjection, the study highlights how depression, suicidal ideation, and encounters with “failed selves” destabilise the boundaries of identity, reflecting the abject dimensions of modern subjectivity (Kristeva 2). Michel Foucault’s concepts of disciplinary power and heterotopia further illuminate the library’s regulated structure, demonstrating how freedom, choice, and self-optimisation operate as subtle mechanisms of control and internalised surveillance (Foucault, Discipline and Punish 202; “Of Other Spaces” 24). By situating The Midnight Library within the evolving Neo-Gothic tradition, this study argues that Gothic motifs of liminality, confinement, and haunting are effectively adapted to interrogate late-modern anxieties, psychological distress, and socio-cultural regulation.
Keywords: Neo-Gothic; Cultural Anxiety; Abjection; Power and Discipline; Matt Haig